Proceedings of the Ninth International Conference on Soft Computing and Pattern Recognition (SoCPaR 2017) - Abraham, Ajith; Haqiq, Abdelkrim; Muda, Azah Kamilah; Gandhi, Niketa (Advances in Intelligent Systems and Computing, 2018)
This book presents 18 carefully selected papers from the ninth edition of the International Conference on Soft Computing and Pattern Recognition (SoCPaR 2017), which was held in Marrakesh, Morocco from December 11 to 13, 2017. A premier conference in the Soft Computing field, SoCPaR brings together the world's leading researchers and practitioners interested in advancing the state of the art in Soft Computing and Pattern Recognition, allowing them to exchange notes on a broad range of disciplines. The book offers a valuable reference guide for all researchers, students and practitioners in the fields of Computer Science and Engineering.